1975
DOI: 10.1080/0002889758507348
|View full text |Cite
|
Sign up to set email alerts
|

Elevated urinary phenol levels not related to benzene exposure

Abstract: Two common over-the-counter medications may elevate urinary phenol to levels exceeding 75 mg/liter (ppm). This study presents data indicating that it is invalid to correct urinary phenol levels to specific gravity of 1.024. Animal studies indicate that having elevated urinary phenol levels secondary to phenyl salicylate ingestion are not harmful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1976
1976
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…[71][72][73][74] Of more importance to the general population is the use of some over-the-counter medications such as Pepto-Bismol and Chloraseptic lozenges. 75 In a trial of Pepto-Bismol, urinary phenol concentration increased over 40-fold, reaching a concentration of 260 p.p.m. in a volunteer who ingested 1 oz of Pepto-Bismol every hour for 8 h Leukemia (Figure 2).…”
Section: Medicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…[71][72][73][74] Of more importance to the general population is the use of some over-the-counter medications such as Pepto-Bismol and Chloraseptic lozenges. 75 In a trial of Pepto-Bismol, urinary phenol concentration increased over 40-fold, reaching a concentration of 260 p.p.m. in a volunteer who ingested 1 oz of Pepto-Bismol every hour for 8 h Leukemia (Figure 2).…”
Section: Medicinesmentioning
confidence: 99%
“…The other important factors affecting reported phenol values are variation in sampling and adjustment for gravity and creatinine. Phenol levels are typically reported as a concentration, mass per mass creatinine, or total mass excreted in 24 h. Data from Refs 47,50,51,54,57,58,75,107,108. flora. Below we discuss these sources and also describe additional host and environmental factors that affect the variability of the background levels of the phenolic compounds.…”
Section: Sources Of Phenol and Hydroquinone In 'Unexposed' Peoplementioning
confidence: 99%
“…The concentration of free urinary phenol peaked at 25 mg/l during the same period. Approximately 60 hours after the first dose, concentrations of both total and free urinary phenol returned to baseline levels (7 and 1 mg/l, respectively) (Fishbeck et al, 1975 …”
Section: Iii1 Hydrolysismentioning
confidence: 99%
“…Approximately sixty hours after the first dose, both total and free urinary phenol levels returned to baseline levels (7 ppm and 1 ppm, respectively). Based on the presented data, for the phenol moiety a total urinary recovery of 130 % could be calculated after subtraction of the baseline phenol excretion (Fishbeck et al, 1975). From the urinary excretion of phenol, it can be concluded that phenyl salicylate is probably completely hydrolysed, either in the GI-tract or after absorption.…”
Section: Ester Hydrolysismentioning
confidence: 99%